An artistic exploration of sand sites in Waterberg, Namibia, as palimpsests of eco-geo-cultural history and identity - Thom, Johan (University of Pretoria, 2021)
Thesis (PhD Fine Arts (Creative Production))--University of Pretoria, 2021.